Eugenia, early Spa nish American science fiction literature, society and futuristic projection (Andamios, Revista de Investigación Social, 2015)
I propose a sociocritic analysis of novel Eugenia. Esbozo novelesco de costumbres futuras to contribute to an explanation of the narrative structure of futuristic utopia in relation to the events narrated, as a result of social concerns of his time. The analysis of the time of writing also aims explain the reasons for the low coverage and the reason that is not part of the canon. Finally, a brief textual analysis, narrative deficiencies will present the text as well as their successes.
Keywords: Eugenia; Urzaiz; science-fiction; literature; society; utopia